PENDEKATAN ARSITEKTUR BERKELANJUTAN DALAM PERANCANGAN BANGUNAN DI TEPI AIR - Citta Parami; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2026)
Waterfront areas in tropical regions face increasing environmental pressures due to coastal urbanization, climate change, and the degradation of aquatic ecosystems. These conditions require architectural approaches that address not only functional and aesthetic aspects, but also environmental sustainability and public space quality. This study aims to identify sustainable architectural principles applicable to tropical waterfront buildings. A qualitative descriptive method was employed through literature review and comparative analysis of two waterfront building precedents that implement sustainability strategies. The analysis was conducted based on resource efficiency, climatic adaptability, and the quality of waterfront public spaces. The findings indicate that passive design strategies, blue–green system integration, and the strengthening of relationships between buildings, public spaces, and water ecosystems are key factors in achieving sustainable waterfront architecture. This study is expected to provide a conceptual foundation for the development of adaptive, ecological, and context-responsive tropical waterfront design. Keywords:  Adaptive; sustainable architecture; water-edge building; tropical; waterfront